2016
DOI: 10.1155/2016/6787854
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Factors and Associations with Postoperative Respiratory Failure, ICU Length of Stay, and Short-Term Survival after Liver Transplantation in a High MELD Population

Abstract: Changes in distribution policies have increased median MELD at transplant with recipients requiring increasing intensive care perioperatively. We aimed to evaluate association of preoperative variables with postoperative respiratory failure (PRF)/increased intensive care unit length of stay (ICU LOS)/short-term survival in a high MELD cohort undergoing liver transplant (LT). Retrospective analysis identified cases of PRF and increased ICU LOS with recipient, donor, and surgical variables examined. Variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…Among the identified PRF risk factors, MELD at transplant, restrictive lung pattern and use of VVBP resulted the most relevant. The role of MELD [13,14,17] and restrictive lung pattern [16] has been previously evidenced. Notably, our study population includes two well-defined groups: high-MELD no-HCC patients and low-MELD HCC patients, and both groups have similar PRF prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identified PRF risk factors, MELD at transplant, restrictive lung pattern and use of VVBP resulted the most relevant. The role of MELD [13,14,17] and restrictive lung pattern [16] has been previously evidenced. Notably, our study population includes two well-defined groups: high-MELD no-HCC patients and low-MELD HCC patients, and both groups have similar PRF prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Length of stay following liver transplantation is currently coming into focus. Several recent studies have identified predictors of prolonged length of stay and have used length of stay as a surrogate for healthcare expenditures …”
Section: Introductionmentioning
confidence: 99%
“…Recently, benchmark 16 indicators have been described regarding outcomes after liver transplant, including surgical outcomes, patient and graft survival, patient care in the ICU, complications, length of stay, and other factors. Regarding length of stay in the ICU, Pedersen and associates, 17 in a study of factors associated with a longer stay in the ICU, found that pretransplant MELD was the most potent predictor of prolonged ICU stay. Stratigopoulou and colleagues 18 confirmed that MELD and transplant duration are independent predictors of prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 99%